The effectiveness of mosque-based women's economic empowerment through the "Mawar Emas" program by the west nusa tenggara sharia economic community on Lombok Island - Yusril Ihza Mahendra; Musawwar; Herawati Khotmi (Enrichment : Journal of Management, 2023)
The poverty which has been born for hundreds of years in Indonesia makes a social phenomenon which is always relevant to be studied. It is added with the fourth largest population in the world which creates a poverty, so it makes multidimensional crisis. One of solutions that can be done to reduce poverty is to empower the community's economy. The objective of this research was to analyze the empowerment model of the Mawar Emas and its effectiveness. This research used descriptive qualitative approach and data collection procedures used observation, interviews, and documentation. Data collection techniques used data reduction, data description, and drawing conclusions. The results of the research showed that the model of the Mawar Emas program was the women’s economic empowerment based on mosques by MES NTB which could help community who wanted to improve their economy. Empowerment was given to women who were at the age of 20 years who were in debt to creditor or who wanted to open a business and increase business capital could be covered. In addition to providing business capital, this program also allowed mosques to carry out their functions in empowering the community's economy with all regulations from forming the groups, returning the capital and business assistance was carried out at mosques.